Design and analysis considerations for thorough QT studies employing conventional (10 s, 12-lead) ECG recordings. Issue 6 (November 2008) - Beasley Jr, Charles M; Dmitrienko, Alex; Mitchell, Malcolm I
The QT interval from the ECG cannot be measured precisely. The relationship of the QT interval to the RR interval within individuals across time and different RR values, and across individuals eludes complete understanding. Intrinsic beat-to-beat variability in QT interval corrected for heart rate (QTc interval) is not trivial. Therefore, it is difficult to determine a valid and reliable estimate of the time for ventricular repolarization based on the QTc interval. Yet, it must be demonstrated that a drug does not result in an increase in the QTc interval that exceeds 5 ms with some reasonable degree of certainty to be quite confident that the drug does not convey some risk of ventricular tachydysrhythmia due to delayed ventricular repolarization. This demonstration can be a Herculean task due to the magnitude of variability in the QTc interval. Design features and analytical methods that might be used in the thorough QT study to improve the chances of demonstrating the true relationship between a drug and QTc interval are reviewed.